2020
DOI: 10.1088/1367-2630/ab9ce7
|View full text |Cite
|
Sign up to set email alerts
|

Covariance matrix entanglement criterion for an arbitrary set of operators

Abstract: A criterion for entanglement detection based on covariance matrices for an arbitrary set of observables is formulated. The method generalizes the covariance matrix entanglement criterion by Simon (2000 Phys. Rev. Lett. 84 2726) to a more general set of operators using the positive partial transpose test for the covariance matrix. The relation is found by starting from the generalized uncertainty relation for multiple operators, and taking the partial transpose on the bipartition. The method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…It is shown that a stricter entanglement condition is provided by the SRUR, using positive partial transpose for non-Gaussian entangled states 42 , 43 and using covariance matrix entanglement criterion for Gaussian entangled states 44 . This has been later generalized by V Tripathi et al 45 .…”
Section: Introductionmentioning
confidence: 79%
“…It is shown that a stricter entanglement condition is provided by the SRUR, using positive partial transpose for non-Gaussian entangled states 42 , 43 and using covariance matrix entanglement criterion for Gaussian entangled states 44 . This has been later generalized by V Tripathi et al 45 .…”
Section: Introductionmentioning
confidence: 79%
“…For k = l = 1 we recover the Gaussian CM and the correlations between standard quadratures. Our HO CM fulfills the following compact form of the uncertainty principle for arbitrary chosen orders k and l [63][64][65]:…”
Section: High-order Quadratures For Non-gaussian Systemsmentioning
confidence: 99%
“…Note that the above covariance matrix C(ψ) expresses fundamental uncertainty relations between the observables O k in the operator pool via the matrix inequation C ≥ 0 [18]. We remark that our definition above of a covariance matrix has complex entries: While this definition will simplify our following arguments, it is worth noting that in the literature other conventions are also commonly used [16][17][18]. For example, ref.…”
Section: A Preliminaries: Operator Covariances and Their Propertiesmentioning
confidence: 99%
“…In contrast to usual variational minimisation of a single cost function, we leverage the following observation: in order to find an eigenstate a large number of properties of the variational quantum state must satisfy certain uncertainty relations with respect to observable measurements. We define these properties as covariances [16][17][18] between the problem Hamiltonian and elements of an operator pool of our choice. This definition leaves us great flexibility in choosing our operator pools and the ability to pose the problem of finding eigenstates as joint roots of all possible covariances.…”
Section: Introductionmentioning
confidence: 99%